2017
DOI: 10.1016/j.clon.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Radiotherapy Technology

Abstract: Many low- and middle-income countries, together with remote and low socioeconomic populations within high-income countries, lack the resources and services to deal with cancer. The challenges in upgrading or introducing the necessary services are enormous, from screening and diagnosis to radiotherapy planning/treatment and quality assurance. There are severe shortages not only in equipment, but also in the capacity to train, recruit and retain staff as well as in their ongoing professional development via effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…According to the 2014 report of the International Agency for Research on Cancer (IARC), about 1.4 million new cancer patients were added from 2008 to 2012 and it was estimated that the number of cancer cases will increase to 25 million in the next 20 years [ 2 ]. Currently, the primary methods for cancer treatment are surgical resection, radiotherapy, chemotherapy, immunotherapy and so on [ 3 , 4 , 5 , 6 ]. Surgical resection temporarily removes the lesion, which cannot be completely removed due to the strong metastatic characteristic of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2014 report of the International Agency for Research on Cancer (IARC), about 1.4 million new cancer patients were added from 2008 to 2012 and it was estimated that the number of cancer cases will increase to 25 million in the next 20 years [ 2 ]. Currently, the primary methods for cancer treatment are surgical resection, radiotherapy, chemotherapy, immunotherapy and so on [ 3 , 4 , 5 , 6 ]. Surgical resection temporarily removes the lesion, which cannot be completely removed due to the strong metastatic characteristic of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Figure reproduced with permission from Feain et al. (2017) . [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…Four materials were used for each patient phantom. All patients used air and skeletal muscle, while the breast and lung patients also used inflated lung and ribs (2)(3)(4)(5)(6), and the prostate patient used gastrointestinal tract and femoral bone. All material composition definitions were taken from International Commission on Radiological Protection (ICRP) data 23 and converted into material files used by DOSXYZnrc.…”
Section: C2 Kvat Dose Calculations and Optimizationmentioning
confidence: 99%
“…Studies have suggested a lack of adequate access to radiation therapy (RT) in low and middle‐income countries (LMICs) . One study, by Datta et al., estimates that by 2020 these countries may have a deficit of approximately 9000 medical linear accelerators (linacs) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation